2020
DOI: 10.1021/acs.chemmater.0c01089
|View full text |Cite
|
Sign up to set email alerts
|

Na2SO4-Regulated High-Quality Growth of Transition Metal Dichalcogenides by Controlling Diffusion

Abstract: The high diffusion rate of sulfur with respect to metal oxide creates precursors that deviate from the stoichiometric ratio, leading to poor growth controllability and defects in the as-grown transition metal dichalcogenides (TMDCs). The introduction of a sulfur precursor with a high melting point is a hopeful strategy to solve these problems. Here, we first introduce sodium sulfate (Na 2 SO 4 ) as a sulfur precursor, which plays roles in tuning diffusion of source precursors and balancing their mass flux base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…[22,[37][38][39] Na species were probably removed as vaporized Na 2 O, Na 2 SO 3 , or Na 2 S after a chemical reaction between molten Na 2 MoO 4 and S-containing admolecules (Figure S14, Supporting Information). [21,39,40] Small 2022, 18, 2106368…”
Section: Resultsmentioning
confidence: 99%
“…[22,[37][38][39] Na species were probably removed as vaporized Na 2 O, Na 2 SO 3 , or Na 2 S after a chemical reaction between molten Na 2 MoO 4 and S-containing admolecules (Figure S14, Supporting Information). [21,39,40] Small 2022, 18, 2106368…”
Section: Resultsmentioning
confidence: 99%
“…[ 39 ] Some literature reported that H 2 reacted with chalcogenides in sulfides and then promoted the growth of 2D TMDC nanoplates. [ 40 ]…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, we use metal precursors (e.g., Pt, Nb, and Ru) with high melting points (>1200 °C), which can provide a steady feeding concentration of metal during the growth process due to their relatively low evaporation capacity at the growth temperature (700–850 °C) (Figure a). On the other hand, we use H 2 S as the non-metal precursor, which provides steady diffusion onto the substrate surface and thus forms a uniform feeding rather than the volcano-like feeding when a solid precursor (e.g., sulfur) is used (Figure b). As the metal precursor has a steady feeding and is immobilized compactly on the substrate, the controllable feeding and diffusion of sulfur into the metal surface will finally result in a vertical composition gradient of sulfur. Consequently, wafer-scale and laterally uniform g-TMDCs could be prepared.…”
Section: Resultsmentioning
confidence: 99%